Instances of Quranic Analysis Using Arabic Linguistic Textual Standards - Muritala, Yahya Toyin (MIR Center for Social-Economic Research, 2013)
The aim of this paper is to highlight some instances of the Quranic Analysis in reference to the modern rules of linguistic textual standards and study the practical indications of the cohesive devices in the analysis of Quranic Arabic texts. Using the descriptive and analytical methods, the research treats the segments of the devices which are reference, substitution, ellipsis, conjunction and lexical cohesion as they are all traceable in the classical Arabic works and the interpretations made on the Quranic Arabic Texts. The paper elaborates on the textual analysis in the language of the Glorious Qur’an in terms of its roles in the deduction of Islamic legal rulings. Likewise, it treats the points of similarities and differences between the various Arabic linguistic analyses which constitute Traditional and Modern methods of textual structuring as related to the Qur’an. The study strikes a balance between the two analytical paradigms and widens the scope of understanding the Quranic message in the modern age. It offers insights into the possible Educational development in the learning of Arabic Language for religious purpose. The paper establishes the importance of analytical specimen from such aspects with attention to the rules guiding the interpretation of the Glorious Quran according to the methods and principles of the early scholars of Islamic Sciences. Finally, it concludes with suggestions and recommendations towards the resolution of the challenges faced in the contemporary Arabic Quranic Learning practices.